[TEX]2sin6x+1=4sin(3x+pi/12)[/TEX]
[TEX]\Leftrightarrow sin6x+\frac{1}{2}=2sin(3x+\frac{\pi}{12})[/TEX]
[TEX]\Leftrightarrow sin6x+sin{ \frac{ \pi }{6}} =2sin(3x+\frac{\pi}{12})[/TEX]
[TEX]\Leftrightarrow 2sinx(3x+\frac{\pi}{12})cos(3x-\frac{\pi}{12})=2sin(3x+\frac{\pi}{12})[/TEX]
[TEX]\Leftrightarrow sin(3x+\frac{\pi}{12})[cos(3x-\frac{\pi}{12})-1]=0[/TEX]
[TEX] \Leftrightarrow \left[sin(3x+\frac{\pi}{12})=0\\cos(3x-\frac{\pi}{12})-1=0[/TEX]
......................................................